แผนยุทธศาสตร์ปฏิรูปการศึกษาสามจังหวัดชายแดนภาคใต้เพื่อสร้างสันติสุข ปี พ.ศ. 2548 – 2551: ศึกษากรณีความสัมพันธ์เชิงอำนาจกับกระบวนการกำหนดนโยบายการศึกษา - สุภาค์พรรณ ตั้งตรงไพโรจน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2018)
The purposes of this research are to 1) study the causes and factors of creating the Three Southern Border Provinces Educational Reform Strategic Plan to create peace during 2005 – 2008 and 2) Analyze the impact of power relations on the formulation of the Three Southern Border Provinces Educational Reform Strategic Plan during 2005 – 2008 by using qualitative research methods such as document analysis and in-depth interviews that use the policy analysis framework in the agenda-setting process and statist model to be the conceptual framework of research. The research found that The reasons and factors in the preparation of the strategic plan are 2 main factors 1) identity factors include 1.1) historical identity and 1.2) cultural identity and 2) political/ security factors consisting of 2.1) public opinion 2.2) the aspects of the ruling class 2.3) influence of political parties 2.4) interest groups 2.5) bureaucracy and 2.6) social pressure The most power relationship in this case goes to the statist model because the state has a leading role in policy formulation without any factor or influence of other groups to support or oppose when it pushed any issue. The authorities who can determine and judge the policy has only 4 persons: The Prime Minister, and three Deputy Prime Minister who use their power to push their own issues into the policy agenda while the Prime Minister will decide which direction is suitable to take. So, the supremacy is Police Lieutenant Colonel Thaksin Shinawatra. Finally, the Deputy Prime Minister; Jaturon Chaisaeng, can successfully push the issue into the policy agenda. In order to ensure that the educational policy comes from identifying appropriate problems and achieving practical results. There should be the following guidelines: 1) the groups / organizations involved in education should be participated in identifying problems from the beginning. 2) the process model is the model that should be most appropriate for policies related to education. And 3) if they want the education policy to be in line with the public interests. Those involved in the education industry (including the media) must try to find channels and opportunities to propose issues to the authority in the policy formulation to be informed in various ways such as holding seminars, doing research, and reporting news in public media, etc.